Climate trend and variability: effect on maize production in the Atlacomulco Rural Development District - Cruz-González , Alejandro; Arteaga-Ramírez, Ramón; Sánchez-Cohen, Ignacio; Soria-Ruiz, Jesús; Monterroso-Rivas, Alejandro Ismael; Flores-Magdaleno, Hector (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of this research was to analyze the trends of precipitation, maximum and minimum temperature in the Atlacomulco Rural Development District (DDRA) of the spring-summer agricultural cycle for the corn crop (April-November). The study examines the trend for the period 1985-2017 for 30 weather stations. A non-parametric Mann-Kendall (MK) technique has been used to establish the statistical trend in the series, as well as the Linear Regression parametric test, to determine the magnitude of this trend. It was found that precipitation, maximum temperature and minimum temperature present a non-significant positive trend during the study period, presenting an increase of 8.5, 4.7 and 12.9% respectively. However, by dividing the information into three time series, it was possible to identify a significant decreasing trend for precipitation in the period 2007-2017 and in maximum temperature towards the period 1996-2006. When analyzing the meteorological stations individually, a heterogeneity of trends was found, keeping a relationship between them according to their proximity and geographical conditions. From the analysis, the results confirm that there are changes in the climatic patterns in the DDRA; that influence impact corn production, so; It is necessary the joint participation of farmers and government in adaptation practices to climate change, implementing policies before this emerging and already present phenomenon.